European somalis’ post-migration movements : mobility capital and the transnationalisation of resources (2018)
This book is about the cross-border movements of a specific group of people at a particular moment in their lives and trajectories. It is about migrants who left their country of origin, Somalia, settled in Europe and have since elaborated complex mobility patterns in order to improve their living conditions. Their lives have been shaped by a first, important move across national borders: the one that brought them to Europe, in most cases through asylum channels and following the collapse of their state of origin. This move has led them to being labelled “migrants” or “refugees” and treated accordingly. They are part of large waves of migration that European states have mostly tried to avoid. However, because of the international conventions these states have signed, among other reasons, they have accepted these newcomers. Many studies about migrants from poorer countries focus on this particular cross-border movement (the “migration”) and its consequences for settlement and incorporation in the new country. The present research takes a step further: it explores other types of movements, those that Somali migrants may undertake once they have settled in their new country of residence. These “post-migration mobility practices”, as I refer to them, have not raised much attention among migration scholars or policymakers, largely because they do not fit into the common sedentarist narratives about migrants from less economically developed parts of the world to Europe or other powerful regions.